Dampak Kinerja Guru PAI terhadap Hasil Pembelajaran al-Quran di Sekolah Menengah Pertama - Erika Yulia Putri (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2020)
This researcher aims to describe the following: the form of pai teacher performance in junior high school, the picture of the results of Qur'an learning students in junior high school and the impact of Islamic Education Teacher performance on the learning results of students in junior high school. The type of research used in this study is a type of field research that uses qualitative descriptive methods, which describes a research result that matches the data found in the field, research data obtained through interviews, observations and documentation, data processed and analyzed and inferred. This research managed to find: 1) The form of pai teacher performance in junior high school is its important role in helping students face or solve their difficulties in Qur'an learning, 2) the picture of qur'an learning results of students in Junior High School still encounters many difficulties in understanding makhraj, mad and tajwid. 3) The impact of PAI Teacher's performance on the learning outcomes of students in junior high school is the increasing results of Qur'an learning students or by improving the quality of reading of students and it turns out that the better the performance of PAI teachers will have a better impact on the learning results of Qur'an Learners.